2017
DOI: 10.1542/peds.2016-1609
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Saturation Targets in Preterm Infants and Outcomes at 18–24 Months: A Systematic Review

Abstract: CONTEXT: The optimal oxygen saturation target for extremely preterm infants remains unclear.OBJECTIVE: To systematically review evidence evaluating the effect of lower (85%-89%) versus higher (91%-95%) pulse oxygen saturation (SpO 2 ) target on mortality and neurodevelopmental impairment (NDI) at 18 to 24 months. DATA SOURCES:Electronic databases and all published randomized trials evaluating lower versus higher SpO 2 target in preterm infants. STUDY SELECTION:A total of 2896 relevant citations were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 46 publications
0
46
0
2
Order By: Relevance
“…[13] However, this did not take into account the different BSID cutoffs between SUPPORT and the other trials in defining disability; in separate meta-analyses using a uniform BSID cutoff and with additional data provided by the SUPPORT investigators, no difference in the primary outcome was found (Figure 1). [14, 15]…”
Section: Neoprom Results: No Differences In Primary Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…[13] However, this did not take into account the different BSID cutoffs between SUPPORT and the other trials in defining disability; in separate meta-analyses using a uniform BSID cutoff and with additional data provided by the SUPPORT investigators, no difference in the primary outcome was found (Figure 1). [14, 15]…”
Section: Neoprom Results: No Differences In Primary Outcomesmentioning
confidence: 99%
“…[16] In a meta-analysis of outcomes before and after study oximeter software revision, differences in mortality were not seen among more than 3000 infants monitored with the original software. [14, 15] Some have attributed the differences seen following the revised algorithm to better separation between study groups; however, post hoc analyses show no improvement in study group separation following software revision, [17] and no enhancement of treatment effect (mortality differences) among NICUs that achieved better separation. [18] An additional confounder in interpreting the mortality results is that two of the BOOST-II trials were stopped early based on an interim analysis of mortality, [10] thus biasing the results towards this outcome; this may explain why these two trials show the largest differences in death between study groups in the NeOProM collaborative.…”
Section: Neoprom Results: Secondary Outcomes Raise Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present review, data are lumped together regardless of the algorithm used in the pulse oximeters. Four meta-analyses and systematic reviews of these data have been published [19, 21-23]; data from these are summarized in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality separately showed a significant increase in RR from 1.16 (95% CI 1.03–1.31) [19] to 1.18 (95% CI 1.03–1.36) [23] in the low saturation target group. For NDI alone, no differences were found between both groups (RR 1.01, 95% CI 0.93–1.09).…”
Section: Introductionmentioning
confidence: 99%